Impact of Blockchain Technology on Efficiency of Financial Transactions - Kotishwar, A. (Indian Journal of Finance, 2020)
Blockchain technology is emerging strong in many areas and is playing a major role in financial transactions, mainly in the banking domain. The study was conducted using primary data by considering the convenient sampling method. The study examined the perceptions on the usage of blockchain technology's implementation with the help of statistical method of discriminant analysis and the results revealed that the perception was higher in case of the attributes such as mitigation of transaction costs and highly secured. The SEM model indicated that smart contracts had a higher impact on the efficiency of financial transactions followed by digital currency. This paper will be useful to the various financial institution regulators, stakeholders, and academicians.